1996
DOI: 10.1097/00004647-199609000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Hyperexcitability and Reduction of GABAA-Receptor Expression in the Surround of Cerebral Photothrombosis

Abstract: Changes of neuronal excitability and gamma-aminobutyric acid (GABAA)-receptor expression were studied in the surround of photothrombotic infarcts, which were produced in the sensorimotor cortex of the rat by using the rose bengal technique. In a first series of experiments, multiunit recordings were performed on anesthetized animals 2-3 mm lateral from the lesion. Mean discharge frequency was considerably higher in recordings from lesioned animals (> 100 Hz in the first postlesional week) compared with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
180
2
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(203 citation statements)
references
References 27 publications
18
180
2
3
Order By: Relevance
“…The observed differences in NPY expression in cortical and subcortical structures may be related to increased glutamate release and neuronal hyperexcitability that occur during the first week after photothrombosis (Buchkremer-Ratzmann and Witte, 1997; Schiene et al, 1996). Importantly, there was no loss of GABAergic interneurons in the cortex (other than within the infarct core) and hippocampus during this time (Frahm et al, 2004), suggesting that increased excitation may be associated with impaired GABAergic mechanisms pre-and/or postsynaptically.…”
Section: Discussionmentioning
confidence: 96%
“…The observed differences in NPY expression in cortical and subcortical structures may be related to increased glutamate release and neuronal hyperexcitability that occur during the first week after photothrombosis (Buchkremer-Ratzmann and Witte, 1997; Schiene et al, 1996). Importantly, there was no loss of GABAergic interneurons in the cortex (other than within the infarct core) and hippocampus during this time (Frahm et al, 2004), suggesting that increased excitation may be associated with impaired GABAergic mechanisms pre-and/or postsynaptically.…”
Section: Discussionmentioning
confidence: 96%
“…In rats with small infarcts, activity within the stroke-affected cortex was required for reaching task performance (Biernaskie et al, 2005). Additionally, structural plasticity is enhanced in perilesional neurons (Stroemer et al, 1995;Gonzalez and Kolb, 2003;Brown et al, 2007), and peri-infarct cortex is hyperexcitable after stroke (BuchkremerRatzmann et al, 1996;Schiene et al, 1996;Mittmann et al, 1998;Neumann-Haefelin et al, 1998Redecker et al, 2002;Carmichael, 2003;Centonze et al, 2007), creating an environment suitable for functional rewiring. Enlarged receptive fields in neurons in somatosensory (Jenkins and Merzenich, 1987;Reinecke et al, 2003) cortices after focal lesions were suggested by extracellular recordings during sensory stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding mechanism, long-lasting neuronal hyperexcitability in peri-infarct cortex is observed after stroke (Domann et al, 1993;Buchkremer-Ratzmann et al, 1996;Schiene et al, 1996;Mittmann et al, 1998;Neumann-Haefelin et al, 1998Redecker et al, 2002), peaking 4 weeks after stroke and persisting for 60 d (Mittmann et al, 1998). Zepeda et al (2004) demonstrated that regional reorganization 5 weeks after photothrombosis correlates with an increase in NMDA-receptor subunit levels from 1-5 weeks after stroke, while GABA levels remain reduced.…”
Section: Models For Functional Rewiringmentioning
confidence: 99%
“…Recent evidence demonstrates that axonal sprouting occurs in the peri-infarct area. 28,29 Based on more recent data, a picture is emerging in the peri-infarct cortex of an evolving environment, in which growth inhibition is suppressed for about 1 month post-infarct. This period is followed by "waves" of growth promotion which may modulate the brain's self-repair processes.…”
Section: Local Plasticity After Lesions In the Motor Cortexmentioning
confidence: 99%